Effects of recombinant human erythropoietin (rHuEPO) on fuel oxidation during rest-work transition in endurance trained athletes - Perrey, S.; Connes, P.; Helmi, B.-S.; Mercier, J.; Caillaud, C. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Some evidence in the literature tend to show a possible impact of recombinant human erythropoietin (rHuEPO) on lipid-carbohydrate metabolism during submaximal exercise (Manitius et al., 1995; Cayla et al. 1999). As endurance training, rHuEPO could induce important changes in muscles energetic metabolism during exercise. Molé and Hoffmann (1999) proposed that breath-by-breath oxygen uptake (VO2) at the early onset of submaximal exercise increases as a biexponential and quantitatively represents the dynamics of intramuscular tryglycerides and carobohydrate oxidation during rest-work transition. The aim of our study was to test the hypothesis that effects of 4 weeks of rHuEPO treatment could lead to higher fat oxidation at the onset of submaximal exercise for a given absolute workload compared with before treatment by using the model of Molé and Hoffmann (1999). Methods Sixteen endurance-trained men were randomly assigned to a group treated with rHuEPO injected subcutaneously three times weekly for four weeks (n=9, EPO) and to a placebo group (n=7, PLA). Each subject performed an incremental maximal exercise pre-treatment, and two 10-min constant cycling exercises (at 45% and 65% maximal VO2). Ventilatory variables and respiratory exchange ratio (RER) were continuously sampled breath-by-breath by an automated system (Jaeger Oxycon Alpha, Hoechberg, Germany). Then we used the VO2 kinetic model from Mole and Hoffman (1999) during the first 300 s of rest-work exercise transition: VO2(t) = alpha(R) + alpha(F)(1 - exp[(t - TD)/-tau(F)]) + alpha(C)(1 - exp[(t - TD)/-tau(C)]), where VO2(t) describes the time course, alpha(R) is resting VO2, t is time after onset of exercise, TD is time delay, alpha(F) and tau(F) are asymptote and time constant, respectively, for the fast (fat) oxidative term, and alpha(C) and tau(C) are the corresponding parameters for the slow oxidative term. Results Parameters of the VO2 kinetics model are reported in the table 1. This study mainly showed that for RER < 1.0, four weeks of subcutaneous rHuEPO injection lead to higher fat oxidation and lower carbohydrate oxidation at the onset of submaximal exercise performed at a given absolute workload compared with before treatment and with PLA group. Discussion/conclusion Whatever the mechanisms involved, it seems that repeated injections of rHuEPO lead to important metabolic adaptations during early exercise that should allow athletes to rather use fat than carbohydrate substrates for a given absolute workload.